2010
DOI: 10.1016/j.jpainsymman.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The Zimbabwe Rural Palliative Care Initiative: PCI-Z

Abstract: The Zimbabwe Rural Palliative Care Initiative is a program to increase access and expand palliative care in rural Zimbabwe. The goal was to add palliative care to existing home-based care teams comprising indigenous rural volunteers. Palliative care expertise is being developed through training and ongoing mentorship provided by Island Hospice Service, headquartered in the capital city of Harare. Specific outcomes relative to palliative care are reported, using the African Palliative Care Association African P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Studies from other African countries have confirmed the value of volunteer work in hospice and palliative care. In Zimbabwe community volunteer training has been shown to be effective, but there is an identified need for close supervision and continuous training [18].…”
Section: Palliative Care Volunteers In Africa and Worldwidementioning
confidence: 99%
“…Studies from other African countries have confirmed the value of volunteer work in hospice and palliative care. In Zimbabwe community volunteer training has been shown to be effective, but there is an identified need for close supervision and continuous training [18].…”
Section: Palliative Care Volunteers In Africa and Worldwidementioning
confidence: 99%
“…34e44 Of the observational studies, 10 were cross-sectional, 6,13,15,16,20,21,23,25,31,32 11 were longitudinal, 11,12,17e19,22,26,27,29,30,33 two were qualitative or mixed methods, 24,28 and one was of part of a quality assurance program. 14 Of the experimental studies, three were randomized controlled trials (RCTs) 37,38,43 and the remainder were quasiexperimental. 34e36,39e42,44 Of the eight STAS studies included, seven were observational 45e51 and one was experimental.…”
Section: Study Designs and Aimsmentioning
confidence: 99%
“…6 The study using POS-S-renal 6 added nine items to the scale to capture additional symptoms in a renal transplant population, whereas a study assessing heart failure and lung cancer patients 21 used the core POS with POS-S, with the addition of two items from POS-S-PP. There were 12 studies reporting use of the African Palliative Care Association (APCA) African POS, 14,16,17,19,20,24,25,31,32,34,38,43 in comparison to just two in the previous review.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations